2010
DOI: 10.1007/s00414-010-0510-0
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of glucose metabolism: post mortem analyses in forensic cases–part II

Abstract: In continuation to part I, a literature review is presented concerning biochemical problems of forensic post mortem cases of unclear hyperglycaemia or hypoglycaemia. Clinical parameters for this purpose were recently reviewed. Particular attention was paid to the detection of diabetic ketoacidosis, of hyperosmolar coma, insulinoma, insulin-induced or oral diabetic-induced hypoglycaemia. The second part of the review discusses the analytes ketone bodies, synthetic insulins, human insulin, C-peptide, proinsulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 129 publications
2
33
0
Order By: Relevance
“…KernbachWighton and Püschel [82] proposed the lower limit of 100 μUI/ml for lethal insulin dosage. Musshoff et al [13] reported that clearly elevated serum insulin levels could be caused by intentional insulin overdose, because levels of 1,000 μUI/ml are rarely seen in patients with insulinsecreting tumours. Karlovsek [37,38] proposed a summary of the biochemical indicators which would support the hypothesis of hypoglycaemia at the time of death, including low or indeterminate glucose concentration in vitreous immediately after death; extremely low glycated haemoglobin in treated diabetics as a consequence of repeated hypoglycaemic states and biochemical and toxicological findings indicating insulin or anti-diabetic overdose.…”
Section: Insulin and C Peptidementioning
confidence: 98%
See 3 more Smart Citations
“…KernbachWighton and Püschel [82] proposed the lower limit of 100 μUI/ml for lethal insulin dosage. Musshoff et al [13] reported that clearly elevated serum insulin levels could be caused by intentional insulin overdose, because levels of 1,000 μUI/ml are rarely seen in patients with insulinsecreting tumours. Karlovsek [37,38] proposed a summary of the biochemical indicators which would support the hypothesis of hypoglycaemia at the time of death, including low or indeterminate glucose concentration in vitreous immediately after death; extremely low glycated haemoglobin in treated diabetics as a consequence of repeated hypoglycaemic states and biochemical and toxicological findings indicating insulin or anti-diabetic overdose.…”
Section: Insulin and C Peptidementioning
confidence: 98%
“…This results in further mobilisation of liver glycogen and the release of glucose into blood circulation as a counterbalancing phenomenon. Considering the difficulty in interpreting postmortem blood glucose levels, other biological fluids, such as vitreous humor and cerebrospinal fluid, have been proposed in order to estimate the antemortem blood glucose concentrations [1,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Glucose Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…23,24 However, insulin levels can be measured in postmortem serum or urine if there is suspected insulin overdose. 25 Toxicological testing of premortem or postmortem serum can detect some drugs, including theophylline, narcotics, and digoxin. If a medication dilution or mixing error is suspected, or a wrong-drug administration is possible, save all syringes, intravenous fluid bags, and bottles in the patient's room for possible testing.…”
Section: Subarachnoid Hemorrhagementioning
confidence: 99%